(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study presents a cognitive linguistic analysis of metaphorical structures embedded in English and Uzbek proverbs and idiomatic expressions, with the aim of uncovering how different linguistic communities conceptualize abstract ideas through metaphor. Rooted in Conceptual Metaphor Theory, the research addresses a critical gap in cross-linguistic metaphor studies by integrating cultural semantics and syntactic analysis. Utilizing a corpus of 200 expressions (100 from each language), the study applies the Metaphor Identification Procedure (MIP) to classify metaphors by type, structure, and cultural salience. The results reveal both universal patterns—such as “LIFE IS A JOURNEY”—and distinct cultural frames, such as the prominence of “COMMUNITY IS FAMILY” in Uzbek, reflecting collectivist traditions, versus “TIME IS MONEY” in English, mirroring individualist, capitalist values. Structural analysis indicates that English idioms allow syntactic flexibility, while Uzbek expressions follow rigid SOV patterns. These findings have theoretical implications for metaphor theory and cultural linguistics, confirming that metaphor functions as a culturally modulated cognitive mechanism. Practically, they inform fields such as translation studies, language pedagogy, and intercultural communication by emphasizing the need to preserve metaphorical meaning across languages. Future research should explore metaphor evolution in digital discourse and among bilingual speakers using computational and interdisciplinary approaches. This study contributes to a deeper understanding of how metaphor bridges language, thought, and culture.